La experiencia laboral de colombia con el covid-19: análisis de las medidas tomadas frente a la crisis, la digitalización y las cifras de empleo en el país - López Moreno, Juan Pablo (2021)
The presence of COVID-19 in Colombia has brought significant impacts in terms of employment. This paper addresses the Colombian experience from a labor and employment stand to approach the crisis generated by Covid-19. Thus, the paper explains the employment measures taken by the Colombian Government to protect employment, the importance of digitalizing work markets in the country, and the impacts on the country’s employment statistics hitherto.